The Protective Effect of Fluorofenidone against Cyclosporine A-Induced Nephrotoxicity - Yang Chen; Nasui Wang; Qiongjing Yuan; Jiao Qin; Gaoyun Hu; Qianbin Li; Lijian Tao; Yanyun Xie; Zhangzhe Peng (Karger Publishers, 2019)
Background/Aims: Cyclosporine A (CsA) is an immunosuppressant drug that is used during organ transplants. However, its utility is limited by its nephrotoxic potential. This study aimed to investigate whether fluorofenidone (AKF-PD) could provide protection against CsA-induced nephrotoxicity. Methods: Eighty-five male Sprague-Dawley rats were divided into 5 groups: drug solvent, CsA, CsA with AKF-PD (250, 500 mg/kg/day), and CsA with pirfenidone (PFD, 250 mg/kg/day). Tubulointerstitial injury index, extracellular matrix (ECM) deposition, expression of type I and IV collagen, transforming growth factor (TGF)-β1, platelet-derived growth factor (PDGF), Fas ligand (FASL), cleaved-caspase-3, cleaved-poly(ADP-ribose) polymerase (PARP)-1, and the number of transferase-mediated nick end-labeling (TUNEL)-positive renal tubule cells were determined. In addition, levels of TGF-β1, FASL, cleaved-caspase-3, cleaved-PARP-1, and number of annexin V-positive cells were determined in rat proximal tubular epithelial cells (NRK-52E) treated with CsA (20 μmol/L), AKF-PD (400 μg/mL), PFD (400 μg/mL), and GW788388 (5 μmol/L). Results: AKF-PD (250, 500 mg/kg/day) significantly reduced tubulointerstitial injury, ECM deposition, expression of type I and IV collagen, TGF-β1, PDGF, FASL, cleaved-caspase-3, cleaved-PARP-1, and number of TUNEL-positive renal tubule cells in the CsA-treated kidneys. In addition, AKF-PD (400 μg/mL) significantly decreased TGF-β1, FASL, cleaved-caspase-3, and PARP-1 expression in NRK-52E cells and further reduced the number of annexin V-positive cells. Conclusion: AKF-PD protect kidney from fibrosis and apoptosis in CsA-induced kidney injury.